SISTEM INFORMASI PENAGIHAN TUNGGAKAN HUTANG BERBASIS ANDROID PADA KOPERASI KONSUMEN UTAMA BERKAH MADANI - Komara, Dewi (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
Koperasi Konsumen Utama Berkah Madani is one of the financial institutions that has visions of becoming an excellent, trustworthy, independent, and healthy financial institution in order to prosper the economy of its members in particular and the society in general. One of its business areas is selling consumer goods at relatively cheap prices but in good quality with cash or in installments. The problems it currently encountered are all the datas such as customer informations, debt collections, and transaction datas are still being recorded manually which are prone to being lost and damaged. This causes it to take longer time to recap monthly transactions. The purpose of this research is to analyze and design an Android-based Debt Collection Information System at Koperasi Konsumen Utama Berkah Madani. The methods used by the author are observations, interviews and literature study. As, the analysis and the system design uses Unified Modeling Language (UML). The conclusions of this research are : 1. The application consists of web (back-end) and Android (front-end) which can be accessed in realtime with the same server. 2. Designing an Android-based information system can help it record all the data it needs.